Performance-Enhancing Substance Use and Intimate Partner Violence: A Prospective Cohort Study - Ganson, Kyle T. (Journal of interpersonal violence, 2022)
Research has shown that performance-enhancing substance (PES) use, including anabolic-androgenic steroids (AAS), is associated with interpersonal violence (e.g., fighting). This study aimed to determine whether legal PES use and AAS use are associated with intimate partner violence (IPV) involvement cross-sectionally and over seven-year follow-up in a nationally representative prospective cohort study. Data from the National Longitudinal Study of Adolescent to Adult Health (N = 12,288) were analyzed (2021). Logistic regression analyses were conducted to determine the associations between legal PES use and AAS use at Wave III (2001?2002; ages 18?26) and IPV victimization (five variables) and IPV perpetration (five variables) at Wave III and Wave IV (2008?2009; ages 24?32), adjusting for relevant demographic and confounding variables. Results from cross-sectional analyses showed that legal PES use and AAS use were associated with higher odds of both any IPV victimization and sexual IPV victimization, and both any IPV perpetration and physical IPV perpetration by pushing or shoving a partner. Results from prospective analyses showed that AAS use, but not legal PES use, was associated with higher odds of all five IPV victimization variables (any IPV victimization: adjusted odds ratio [AOR] 1.72, 95% confidence interval [CI]1.04?2.84; two forms of physical abuse: 1: AOR 2.01, 95% CI 1.15?3.50; 2: AOR 2.11, 95% CI 1.06?4.21; incurring an injury from IPV victimization: AOR 4.90, 95% CI 1.71?14.01; and sexual IPV victimization AOR 2.44, 95% CI 1.05?5.65), as well as three IPV perpetration variables (any IPV perpetration: AOR 2.11, 95% CI 105?4.23; one form of physical abuse perpetration: AOR 2.58, 95% CI 1.06?6.27; and sexual IPV perpetration: AOR 3.80, 95% CI 1.44?10.02). These results emphasize the adverse social and interpersonal risks associated with PES use. Continued research, health care, and public health prevention and intervention efforts to reduce the use of PES and occurrence of IPV are warranted.